Strong Influence of Changes in Terrestrial Water Storage on Flood Potential in India. Issue 1 (29th December 2020) - Shah, Deep; Mishra, Vimal
Abstract: Rapid groundwater depletion due to anthropogenic pumping for irrigation poses enormous challenges on socio‐economic, agricultural, and financial spheres of India. However, the role of groundwater depletion on flood potential in India remains unexplored. We examine the role of changes in terrestrial water and groundwater storage on flood potential using in situ and Gravity Recovery and Climate Experiment (GRACE) satellites observations and the simulations from the Variable Infiltration Capacity (VIC) model. Terrestrial Water Storage (TWS) has declined significantly ( p value <0.05) with a rate of −0.63 cm yr −1 during 2002–2016 in the Indian subcontinent. Ganga, Brahmaputra, Indus, Brahmani, and Subernarekha river basins experienced a significant decline while Godavari, Mahi, Tapi, and Narmada basins witnessed a substantial increase in TWS during 2002–2016. The relative contribution of TWS on flood potential is higher than precipitation for the majority of the subcontinental river basins. The significant increase/decline in TWS in the subcontinental river basins is driven by the changes in groundwater storage either due to groundwater pumping or natural variability in climate. A significant decrease (increase) in the flood potential in Ganga, Brahmaputra, and Indus (Godavari, Narmada, and Tapi) is linked to the changes in groundwater storage, which shows the influence of groundwater storage variability beyond water and food security in the region. Key Points: Terrestrial Water Storage (TWS) has declined significantly ( p value < 0.05) with a rate of −0.63 cm yr −1 during 2002–2016 in the Indian subcontinent The relative contribution of TWS on flood potential is higher than precipitation for the majority of the subcontinental river basins A significant decrease in the flood potential in Ganga, Brahmaputra, and Indus is linked to groundwater depletion